To What Extent Do Learner‐ and Word‐Related Variables Affect Production of Derivatives?. Issue 1 (18th October 2022) - Iwaizumi, Emi; Webb, Stuart
Abstract: This study explores the effects of receptive derivational affix knowledge, derivative frequency, part of speech, and vocabulary breadth on production of derivatives. Twenty‐one speakers of English as a first language and 107 learners of English as a second language were asked to produce derivatives for 90 prompt words on a decontextualized derivative form‐recall test. Results indicated that (a) increased receptive derivational affix knowledge and derivative frequency were linked to greater accuracy in production of derivatives, (b) adverb derivatives were more frequently produced compared to other parts of speech, and (c) learners' vocabulary breadth was associated with greater accuracy in producing derivatives. Results also indicated a larger facilitative effect of derivative frequency for second language learners in comparison to first language speakers, but this effect diminished as vocabulary breadth increased. These findings suggest that learners may initially acquire derivatives on a case‐by‐case basis but, as their knowledge of derivational affixes and vocabulary breadth increases, they may acquire derivatives more systematically. Abstract : A one‐page Accessible Summary of this article in non‐technical language is freely available in the Supporting Information online and at https://oasis‐database.org